A systematic review of treatments for acne scarring. Part 2: Energy-based techniques - Georgios Kravvas; Firas Al-Niaimi (SAGE Publishing, 2018)
Introduction: Acne scarring is a very common problem, which can be extensive, and may lead to significant psychosocial morbidity. Multiple types of treatments are used to ameliorate atrophic scars with varying degrees of success. This paper provides an overview of the various energy-based modalities that are commonly employed against acne scarring. Objectives and methods: A comprehensive literature search of papers published since 2008 was performed in order to determine the efficacy and adverse reactions of commonly used energy-based treatments against post-acne scarring. Results: A total of 59 relevant articles were identified covering a multitude of different devices. Discussion: Ablative lasers seem to achieve the highest degree of efficacy, albeit this is associated with significant pain and downtime, and the risk for long-term pigmentary changes. Non-ablative fractional photothermolysis (FP) has a much safer profile but cannot achieve as good cosmetic results. The efficacies of fractional radiofrequency microneedling and radiofrequency are slightly inferior to that of FP but offer an even safer adverse profile. Little evidence is available on the remaining devices, with larger studies required in order to reach more solid conclusions. Conclusion: Multiple devices have been used with varying levels of efficacy and very different safety profiles. There is an overall lack of high-quality evidence about the effects of different interventions. Furthermore, no standardised scale is available for acne scarring, leading to variability in evaluation and interpretation of data in different studies.